Tailoring the electron redistribution of RuO2 by constructing a Ru-O-La asymmetric configuration for efficient acidic oxygen evolution - Cong-Hui Li; Cheng-Zong Yuan; Xiaolei Huang; Hongrui Zhao; Fuling Wu; Lei Xin; Xiaomeng Zhang; Shufeng Ye; Yunfa Chen (eScience)
Stabilizing the highly active RuO2 electrocatalyst for the oxygen evolution reaction (OER) is critical for the application of proton exchange membrane water electrolysis, but this remains challenging due to the inevitable over-oxidation of Ru in harsh oxidative environments. Herein, we describe constructing Ru-O-La asymmetric configurations into RuO2 via a facile sol-gel method to tailor electron redistribution and thereby eliminate the over-oxidation of Ru centers. Specifically, the as-prepared optimal La0.1Ru0.9O2 shows a low overpotential of 188 ​mV at 10 ​mA ​cm−2, a high mass activity of 251 A gRu−1 at 1.6 ​V vs. reversible hydrogen electrode (RHE), and a long-lasting durability of 63 ​h, far superior to the 8 ​h achieved by standard RuO2. Experiments and density functional theory calculations jointly reveal that the Ru-O-La asymmetric configuration could trigger electron redistribution in RuO2. More importantly, electron transfer from La to Ru via the Ru-O-La configuration could lead to increased electron density around Ru, thus preventing the over-oxidation of Ru. In addition, electron redistribution tunes the Ru 4d band center’s energy level, which optimizes the adsorption and desorption of oxygen intermediates. This work offers an effective strategy for regulating electronic structure to synergistically boost the activity and stability of RuO2-based acidic OER electrocatalysts.